Forming Children Character from View Person Centered and Al-Qur'an - Nurwahidah Alimuddin; Siti Rahmi; Nurul Fadilah (Department of Guidance and Counseling, FIP, Undiksha, 2021)
The child's religious's mental, and moral development is not a process that can occur quickly and be forced. Still, it must be gradual, reasonable, healthy, and following the growth, abilities, and nature of the age that is being passed. Here, parents must be able to capture the positive trends of child development to be very important. Parents' obligation is to motivate and direct children to a positive outcome, even though the tendency is not following the parents' wishes. This, Islam teaches that in caring for children not to differentiate between boys and girls, eldest or youngest children, normal or abnormal children, parents still provide the same opportunity to obtain educational services following their potential, talents, and interests. Children must be treated fairly and not discriminatory. Hadith of the Prophet Muhammad says that